A Prospective Randomized Comparison of Concurrent Chemoradiation with Neoadjuvant and Adjuvant Chemotherapy with Concurrent Chemoradiation Alone for Locally Advanced Carcinoma Cervix - Singh, Rahul; Bhatt, M LB; Kumar, Rajendra; Srivastava, Kirti; Grover, R K; Shukla, Pragya; Raturi, Vijay P; Roopali; Gaur, Jalaj; Saha, Mandira; Kishan, Dewesh (Indian Journal of Medical and Paediatric Oncology, 2019)
Aims: The aim of this study was to compare concurrent chemoradiation along with neoadjuvant and adjuvant chemotherapy versus concurrent chemoradiation alone in locally advanced cervical cancer regarding treatment response and toxicities. Subjects and Methods: A randomized control study was done on 116 patients with locally advanced carcinoma cervix (Stage IIB to IIIB) registered between January 2014 and February 2015. Patients were randomly divided to receive either one cycle of cisplatin/5-fluorouracil neoadjuvant chemotherapy and two cycles of the same adjuvant chemotherapy with concurrent chemoradiation with weekly cisplatin (Arm A) or only concurrent chemoradiation (Arm B). All patients received three fractions of high-dose-rate intracavitary brachytherapy after completion of the external radiation. Results: A higher proportion of the patients of chemotherapy arm achieved complete response (94%) as compared to the nonchemotherapy arm (56%), and this was statistically significant. There was a trend toward more treatment-related acute toxicity with chemotherapy. Conclusions: These results have corroborated the view that if neoadjuvant and adjuvant chemotherapies are added to concurrent chemoradiation, it could further the effects of concurrent chemoradiation for patients with locally advanced cancer of the uterine cervix.
Keywords: Acute toxicity; adjuvant chemotherapy; complete response; concurrent chemoradiation; locally advanced cervical cancer; neoadjuvant chemotherapy